The incentives in the civil law as a means of improving the management of economic relations - T A Mechetina (RUDN Journal of Law, 2014)
The article focuses on the issues of improving the efficiency of the legal regulation of economic relations. Particular attention is paid to the incentives in the civil law and on their interaction with other civil remedies impact on social relations.